Mr. Stink - Walliams, David 1971-; Blake, Quentin (New York, N.Y Razorbill, 2010)
"Mr. Stink stank. He also stunk. And if it was correct English to say he stinked, then he stinked as well. Chloe sees Mr. Stink every day, but she's never spoken to him. Which isn't surprising, because he's a tramp, and he stinks. But there's more to Mr. Stink than meets the eye (or nose) and before she knows it, Chloe has an unusual new friend hiding in her garden shed. As Chloe struggles to keep Mr. Stink a secret, and her dad tries to hide a secret of his own, the stage is set for an epic family confrontation. But there's one other person with an extraordinary secret Mr. Stink himself"--Publisher's description
Available edition 2009 in misr public library - el zawia el hamara branch
1 13
Keywords: Family life -- Fiction; Friendship -- Juvenile fiction; Homeless persons -- Fiction; Homeless persons -- Juvenile fiction; Secrecy -- Fiction; Tramps -- Fiction; Family life -- Fiction; Homeless persons -- Fiction; Secrets -- Fiction; Tramps -- Fiction; Realistic fiction